Open defecation among adults having household toilets and factors associated with it: An analytical cross-sectional study from rural Bihar, India - Arutperumjothi Muthukumaran; Alok Ranjan; Sanjay Pandey; Pragya Kumar; Rajath Rao (Elsevier, 2024)
Background: Bihar is one of the focus states under Swachh Bharat Mission (SBM) in India. A study was conducted to estimate the prevalence and to determine the factors associated with the practice of open defecation among adults having household toilets, in rural Patna, Bihar. Methods: An analytical cluster cross-sectional study was conducted for a duration of one year among 609 participants using cluster sampling in rural block of Patna. The prevalence was calculated with 95 % confidence interval and binary logistic regression analysis was done to determine factors associated with open defecation. Results: Out of 609, 391(64.2 %, 95 % CI: 60-68 %) were practising open defecation despite having a household toilet. Male gender (AOR, 1.684; 95 % CI, 1.1-2.4), scheduled caste community (AOR, 2.168; 95 % CI, 1.3-3.4), family gross monthly income Rs. <7770 (AOR, 2.838; 95 % CI, 1.6-4.8), age of initiating toilet uses at age >35 years (AOR,1.453; 95%CI, 1.0-2.0), absence of government supply as water source (AOR: 2.106, 95 % CI: 1.088-3.410) were the independent factors associated with practice of open defecation. Conclusions: Nearly two-third of adults were practising OD despite having a household toilet. Male gender, schedule caste community, family gross monthly income Rs. <7770, age of initiating toilet uses at age >35 years, lack of government supply as water source were the factors associated with the practice ofOD.